Formation of special odors driven by volatile compounds during the growth and maturation in edible fungi (Phallus impudicus) - Huijuan Liu; Zhifei Cheng; Jiao Xie (Food Chemistry: X, 2024)
Composition and content of volatiles, the important factors in flavor formation of edible fungi, are affected by growth process. GC–MS was performed and a total of 102 volatiles were identified in Phallus impudicus. Almost all identified volatile compounds showed an obvious upward trend at four growth period, and reached the maximum at fourth stage (PIII), of which the transition from first stage (ZP) to second stage (PI) achieved a breakthrough for 88 volatile compounds from scratch. The PCA and HCA results showed that the four stages were completely separated and appeared different, among which third stage (PII) and PIII might be the two dramatic change nodes in aroma quality. In addition, the top 50 differential metabolites were screened by OPLS-DA and PLS-DA, and correlation analysis showed that 6-undecyl alcohol, α-terpine-7-al, 2, 4-decenol, and 2-cyano-2-ethyl-butanamide, might co-regulate the flavor formation of Phallus impudicus through synergistic action of other chemical components.